Mathematical optimization for economic agents (SCIÉNDO INGENIUM, 2021)
This article aims to make mathematical tools available to economic agents to strengthen their activities. In recent years, optimization techniques, so useful in microeconomic theory, have been expand to incorporate more powerful differential and topological methods, these methods have led to new results on the qualitative behavior of general economic and political systems. The simplest and most common way to describe a company's technology is the production function. However there are other ways of describing company technologies that are more general and more useful in certain settings. In this sense, the rapidity with which changes are taking place in our society are additives that immerse us in the era of automation, for example the "just in time”, production technique is implanting in the business sector the culture of "total quality". The need to improve costs to grow leads to the application of mathematical tools. Thus, in this research we propose tools: (i) The Kuhn - Tucker theorem, (ii) The maximum theorem, (iii) The envelope theorem, together with an application of these.
Keywords: Mathematical Optimization; Mathematical Tool; Economic Agents